Parlamentskii dnevnik . Parlamentskii dnevnik . Parliamentary Diary . Парламентский дневник - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing parliamentary readings and the order of the adoption of federal constitutional laws. Featured in the program: Shumeiko, Vladimir Filippovich (First Deputy Prime Minister of the Russian Federation); Nosovets, Sergei (People's Deputy); Mitiukov, Mikhail Alekseevich (Chairman of the Committee for Legislation of the Supreme Council of the Russian Federation) Contributors: Direktsiia mezhregional'nykh programm (Studio) Разговор о парламентских чтениях и порядке принятия федеральных конституционных законов. В программе участвуют: Шумейко, Владимир Филиппович (Первый заместитель председателя Правительства Российской Федерации); Носовец, Сергей (Народный депутат); Митюков, Михаил Алексеевич (Председатель Комитета по законодательству Верховного Совета РФ) Создатели: Дирекция межрегиональных программ (Студия)